2012
DOI: 10.1002/jccs.201200146
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Selective Amperometric Detection of Periodate at Glassy Carbon Electrode Modified with a Cyclometalated Iridium(III) Complex and Single‐Wall Carbon Nanotubes

Abstract: Single-wall carbon nanotubes (SWCNTs) were used as an immobilization matrix to incorporate [Ir(ppy) 2 (phen-dione)](PF 6 ) complex onto a glassy carbon electrode for the study of electrocatalytic reduction of periodate ion. Detailed preliminary electrochemical data for the Ir(III)-complex in acetonitrile solution and for the modified GCE/SWCNTs/[Ir(ppy) 2 (phen-dione)](PF 6 )/CGE are presented. The modified electrode was applied to selective amperometric detection of periodate through its electrocatalytic redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The experimental findings demonstrated that within the 0–100 μM range, the fluorescence intensity of the 1 ‐H 2 O suspension exhibited an increase corresponding to the rise in CET concentration (Figure 4a). Based on the above, in order to quantitatively study the fluorescence enhancement efficiency, the fluorescence enhancement efficiency K EC is introduced, which is defined as ( I − I 0 )/( I 0 [A]) ([A] is the analyte concentration) 34 . As shown in Figure 4b,c, a strong linear correlation is observed between the ratio of fluorescence intensity ( I / I 0 ) and the concentrations of CET within the 0–50 μM range of CET, but with the increase in CET concentration after 50 μM, the linearity is not ideal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental findings demonstrated that within the 0–100 μM range, the fluorescence intensity of the 1 ‐H 2 O suspension exhibited an increase corresponding to the rise in CET concentration (Figure 4a). Based on the above, in order to quantitatively study the fluorescence enhancement efficiency, the fluorescence enhancement efficiency K EC is introduced, which is defined as ( I − I 0 )/( I 0 [A]) ([A] is the analyte concentration) 34 . As shown in Figure 4b,c, a strong linear correlation is observed between the ratio of fluorescence intensity ( I / I 0 ) and the concentrations of CET within the 0–50 μM range of CET, but with the increase in CET concentration after 50 μM, the linearity is not ideal.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above, in order to quantitatively study the fluorescence enhancement efficiency, the fluorescence enhancement efficiency K EC is introduced, which is defined as (I À I 0 )/(I 0 [A]) ([A] is the analyte concentration). 34 As shown in Figure 4b,c, a strong linear correlation is observed between the ratio of fluorescence intensity (I/I 0 ) and the concentrations of CET within the 0-50 μM range of CET, but with the increase in CET concentration after 50 μM, the linearity is not ideal. In the concentration interval from 0 to 50 μM, the I/I 0 and concentrations of CET conform to the linear equation I/I 0 = [CET] Â 5.4750 Â 10 4 M À1 + 0.98 (R 2 = 0.99803), with the K EC value of 5.4750 Â 10 4 M À1 and the limit of detection (LOD) determined to be 165 nM using the calculation formula 3σ/K EC (σ denotes the standard deviation of the measurement for the blank).…”
Section: Performance In Cet Sensingmentioning
confidence: 87%
“…[42] On the other hand, GSH, as the most abundant non-protein thiol, is a major reductant in internal cellular compartments. [15,43] As a consequence, we chose the structurally related 1,10-phenanthroline-5,6-dione (phendione) moiety as the N^N donor for the iridium(III) complex 1 ,[41] which also coordinates two C^N ligands (ppy). We anticipated that the reduction of the phendione N^N donor by GSH, generating complex 2 , may influence the MLCT state of the iridium(III) complex, thereby allowing 1 to act as a luminescent chemosensor for thiols (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[41] A suspension of [Ir(ppy) 2 ] 2 Cl 2 (ppy = 2-phenylpyridine) (0.2 mmol) and 1,10-phenanthroline-5,6-dione (phendione) (0.42 mmol) in a mixture of CH 2 Cl 2 :MeOH (1:1, 20 ml) was refluxed overnight under N 2 . The product mixture was then allowed to cool down to 25°C, and was filtered to remove unreacted dimer.…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches for periodate detection were available, including electrochemical methods (Chatraei and Zare, 2013;Salimi et al, 2007;Shamsipur et al, 2013) and UV-vis spectrophotometry Benvidi et al, 2012;Ensafi and Chamjangali, 2003;Ni and Wang, 2007). To best of our knowledge, there is no efficient tool reported for discriminating periodate from other forms of iodine species and simultaneous monitoring of concentration changes of periodate with high accuracy.…”
Section: Introductionmentioning
confidence: 99%